Secret To Riches Dalam Perspektif Hadis: Studi Hadis Tematik - Pajriah Pajriah; Muhammad Alif; Masrukhin Muhsin (STIKes Ibnu Sina Ajibarang, 2025)
This article discusses the secret to wealth from the perspective of the Hadith of Prophet Muhammad (peace be upon him), emphasizing the importance of understanding wealth both spiritually and physically. In society, many questions arise regarding how to become wealthy according to Islamic teachings, especially based on the Prophet's hadiths. Therefore, this article aims to provide a Sharia-compliant guide on how to acquire wealth and how to distribute it properly. The discussion focuses on four main points: (1) understanding true wealth that has eternal value in the hereafter, (2) motivation to pursue wealth, (3) factors that attract sustenance, and (4) factors that hinder sustenance. The author highlights the issue that many people desire wealth but pursue it through means prohibited in Islam, such as stealing, engaging in usury, or seizing others' rights. In this context, the hadiths serve as the main foundation for explaining the principles of blessed and lawful wealth. Through this article, the author hopes to provide society with the correct understanding of how to seek worldly wealth while upholding Islamic values. This article is also expected to serve as a guide to build spiritual awareness and ethical conduct in striving for success, and to offer a reflection for both the author and readers on the journey toward halal and blessed wealth.